MODERN YOUTH – THE FOUNDATION OF OUR FUTURE - Toyeva Gulchiroy To'lqinjon qizi; Toyeva Gulchiroy To'lqinjon qizi (TADQIQOTLAR, 2026)
Abstract Youth play a vital role in the development of every society. They are the driving force behind innovation, economic growth, and social progress. This article examines the importance of modern youth in building the future, analyzes their educational and social opportunities, and discusses the challenges they face in the contemporary world.